Digital financial inclusion, digital financial services tax and financial inclusion in the fourth industrial revolution era in africa - Favourate Y. Mpofu; David Mhlanga (Economies, 2022)
The digital economy has risen dramatically in the global environment, and many developing countries, including African countries, have seen a spike in digital activity over recent years. The digital economy's growth has resulted in an increase in digital financial services (DFS) in Africa and other developing regions. Since many African countries are under pressure to raise domestic revenue, taxing the digital economy has become a viable option. As a result, this study attempted to respond to the following questions: first, what is the link between DFS growth and digital inclusion in African countries? Second, what justifies the imposition of DFS taxes in Africa? Third, what are the potential consequences of DFS taxes in African countries? Using secondary data from the literature review and document analysis, a systematic technique for assessing or evaluating printed and electronic documents, and computer-based and internet-transmitted material, the study discovered that digital financial inclusion is driving financial inclusion on the African continent. The study also found that, despite several negative consequences associated with the growth of the digital economy, most African economic activities are informal and are being aided by various digital financial services. Therefore, it is equally crucial that when adopting digital finance taxes, care is taken to avoid excluding low-income earners from the financial sector and to take note of the usage, affordability, and distortive implications of taxation.
Keywords: 330; Africa; Industry 4.0; digital financial services; financial inclusion; taxation